2013
DOI: 10.1007/s00540-013-1699-0
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral dysfunction after coronary artery bypass surgery

Abstract: Cerebral dysfunction after cardiac surgery remains a devastating complication and is growing in importance with our aging populations. Neurological complications following cardiac surgery can be classified broadly as stroke, encephalopathy (including delirium), or postoperative cognitive dysfunction (POCD). These etiologies are caused primary by cerebral emboli, hypoperfusion, or inflammation that has largely been attributed to the use of cardiopulmonary bypass. Preventative operative strategies, such as off-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 88 publications
3
34
1
7
Order By: Relevance
“…These situations resemble locomotive syndrome and frailty in the elderly and hospitalized patients undergoing surgery can be considered to have a high risk of locomotive syndrome and frailty. In addition, the development of delirium and cognitive dysfunction after surgery further deteriorates the patient's physical status due to increased morbidity and hospital length of stay, especially in elderly patients [16,17].…”
Section: The Impact Of Surgery On the Elderlymentioning
confidence: 99%
“…These situations resemble locomotive syndrome and frailty in the elderly and hospitalized patients undergoing surgery can be considered to have a high risk of locomotive syndrome and frailty. In addition, the development of delirium and cognitive dysfunction after surgery further deteriorates the patient's physical status due to increased morbidity and hospital length of stay, especially in elderly patients [16,17].…”
Section: The Impact Of Surgery On the Elderlymentioning
confidence: 99%
“…Stroke incidence after cardiac surgery has been reduced to 1-8%, and delirium incidence to 7-10%, whereas the incidence of cognitive disorders remains 30-80% within one month after surgery, and 10-60% within three-to four months after surgery. However, a significant amount of controversial data is still present in publications on the issue (Goto, & Maekawa, 2014;Trubnikova, Mamontova, Syrova, Maleva, & Barbarash, 2014;Baba, Maekawa, Otomo, Tokunaga, & Oyoshi, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…He also reported that postoperative pain management and intensive early rehabilitation seem to be important for the prevention of POCD in elderly patients. Kengo Maekawa showed that assessment of magnetic resonance images of the brain revealed reduced gray matter bilaterally in the medial temporal lobe, together with white matter lesions in the brains of elderly cardiac surgery patients who developed POCD [30,31]. Kazuyoshi Ishida reviewed >100 previous studies and pointed out that many patients undergoing major vascular surgery under deep circulatory arrest or retrograde cerebral perfusion, and an equal or even larger number of patients undergoing surgery with selective cerebral perfusion, seem to develop POCD when compared with patients after coronary artery bypass grafting [32].…”
Section: Journal Of Anesthesia Symposium 2016mentioning
confidence: 99%